Investigating the defoliating‐like (DL) VCG2A pathotype of Verticillium dahliae through identification and prediction of secreted proteins from genomes of Australian isolates. (4th November 2022) - Webster, John; Dadd‐Daigle, Pearl; Chapman, Toni A.; Kirkby, Karen
Abstract: In Australia, recent investigations have reported the presence of a number of Verticillium dahliae pathotypes (VCG1A, VCG2A and VCG6) that cause disease in cotton and agricultural weeds. During these investigations, it was observed that a VCG2A V . dahliae displayed greater virulence than previously reported in local and international isolates. Genome sequencing of seven V . dahliae isolates was performed using a mixture of short and long reads sequencing technologies. Of these seven isolates, four were identified as D VCG1A, one ND VCG2A, a recently identified Australian VCG6 as well as a virulent VCG2A, classified as "defoliating‐like". The secreted protein repertoire from the genomes of these Australian V . dahliae isolates was predicted using four separate signal prediction methods. The consensus secreted protein set of the isolates revealed the presence of 20 proteins that were present in all virulent isolates, including the virulent DL VCG2A, and absent in the nonvirulent VCG2A isolates. Ten of these proteins had a functional annotation and were identified as ligninase H8, lipolytic enzyme, laccase, amine oxidase, spherulin‐1A, dipeptidyl‐peptidase, monooxygenase, dienelactone hydrolase, carboxypeptidase and fibronectin by BLASTP. Abstract : A defoliating‐like VCG2A Verticillium dahliae isolate was observed to have 20 secreted proteins in common with virulent phenotypes; interestingly half of these were most closely related to proteins from a VCG6 isolate.